2008
DOI: 10.1002/jor.20627
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception assessment in subjects with idiopathic loss of shoulder range of motion: Joint position sense and a novel proprioceptive feedback index

Abstract: ABSTRACT:We examined the effects of elevation range and plane on shoulder joint proprioception in subjects with idiopathic loss of shoulder range of motion (ROM). Joint position sense (JPS) and a novel proprioceptive feedback index (PFI), including difference magnitude and the similarity index, were used to assess proprioception. Twelve subjects (eight male, four female) with involved stiff shoulders and normal opposite shoulders were recruited from a university hospital. Subjects attempted to repeat six targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
1
15
0
1
Order By: Relevance
“…19Y24 Although they are suggested in the rehabilitation of upper extremity problems in everyday practice, research about this subject is limited. 13,25,26 This study is the first randomized controlled research in patients with SIS investigating the effectiveness of proprioceptive exercises on proprioception, clinical, and functional assessments. The authors found a significant improvement in terms of pain, ROM, function, muscle strength, and proprioceptive assessment in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…19Y24 Although they are suggested in the rehabilitation of upper extremity problems in everyday practice, research about this subject is limited. 13,25,26 This study is the first randomized controlled research in patients with SIS investigating the effectiveness of proprioceptive exercises on proprioception, clinical, and functional assessments. The authors found a significant improvement in terms of pain, ROM, function, muscle strength, and proprioceptive assessment in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The sensors for the system were attached to bony landmarks with adhesive tape and Velcro straps. These surface sensor placements were the sternum, the flat superior bony surface of the scapular acromial process, and the distal humerus between the lateral and medial epicondyles 13. A fourth sensor, attached to a stylus, was used to digitize palpated anatomical coordinates (bony landmarks: sternal notch, xiphoid process, 7th cervical vertebra, eighth thoracic vertebra, acromioclavicular joint, root of the spine of the scapula, inferior angle of the scapula, and lateral and medial epicondyles; the glenohumeral joint rotation center was operationalized by the anterior humeral joint and posterior humeral joint) 19, 20.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis, proprioceptive feedback index (PFI)13 was calculated from the mean of the 4th, 5th, and 6th trials. The PFI comprised two values: one derived from the total absolute angle difference between targeted movement and reproduced trials of movements (the sum of 10% movement difference, square root of ((target − reproduced plane) 2 + (target − reproduced elevation) 2 + (target − reproduced axial rotation) 2 recorded for movement (proprioceptive feedback magnitude, PFM); the other is derived from the correlation between instant movement and prototype instant movement on arm elevation (similarity index, SI) 13. An instant movement was generated from every 10% of the movement based on time by averaging across each trial of each test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other results suggest that capsule ligamentous and musculotendinous mechanoreceptors in the shoulder joint have significant function in proprioception feedback during active movements in subjects with idiopathic loss of range of motion in the shoulder [31]. …”
Section: Discussionmentioning
confidence: 99%